Respuesta :

Answer:

see below

Step-by-step explanation:

4. ( x+3) ( x-5)

FOIL

   x*x - 5x + 3x -15

Combine like terms

  x^2 -2x-15

5.  ( 2x-4) ( 3x-7)

FOIL

  2x*3x  -7*2x  -4*3x +28

6x^2 -14x -12x +28

Combine like terms

6x^2 -26x +28

6.  ( 3x^2 +2x+1) ( x+3)

Distribute

3x^2*x + 3x^2*3  + 2x*x + 2x*3  + x+3

3x^3 +9x^2 +2x^2 +6x+x+3

Combine like terms

3x^3+11x^2+7x+3

Step-by-step explanation:

Hey there!

4. (x+3) (x-5)

Multiply them.

[tex] = x(x - 5) + 3(x - 5)[/tex]

Simplify them to get answer.

[tex] = {x}^{2} - 5x + 3x - 15[/tex]

[tex] = {x}^{2} - 2x - 15[/tex]

5. (2x-4) (3x-7).

Multiply them and simplify to get answer.

[tex] = 2x(3x - 7) - 4(3x - 7)[/tex]

[tex] = 6 {x}^{2} - 14x - 12x + 28[/tex]

[tex] = 6 {x}^{2} - 26x + 28[/tex]

6. (3x^2 +2x +1) (x +3)

Multiply them and simplify them to get answer.

[tex]x(3 {x}^{2} + 2x + 1) + 3(3 {x}^{2} + 2x + 1)[/tex]

[tex] = 3 {x}^{3} + 2 {x}^{2} + x + 9 {x}^{2} + 6x + 3[/tex]

[tex] = 3 {x}^{3} + 11 {x}^{2} + 7x + 3[/tex]

Hope it helps..

ACCESS MORE